SPECIFIC FEATURES OF POWER CONSUMPTION OF LED DEVICES AND ACCOUNTING THEM IN CALCULATION OF ELECTRICAL NETWORKS - V. N. Radkevich; Ya. V. Michailova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The indicators of power consumption of lighting devices based on LEDs are studied depending on the supplied voltage. For the lamp and floodlight with LEDs active and reactive power, current and power factor as a function of voltage (which value changed in the range 200–245 V) were experimentally determined. The analysis of experimental data demonstrated that due to the drivers in the specified voltage range the active power consumed by light devices remains practically unchanged. The reactive power of LED devices depends on the supplied voltage and is capacitive in its nature. In contrast with gas-discharge light sources the LED devices under study do not consume reactive power, but generate it. With the change of the supplied voltage from 200 to 245 V the value of the generated reactive power increases to 60 % for the floodlight and 50 % for the lamp. The LED floodlight has a low coefficient of active power. The current consumed by the floodlight has increased by 22 %, and by the lamp – by 13 %. The formulas for determining the maximum value of the length of the calculated section of single-phase group lines were developed, taking into account specific source data. LED light sources tend to feed by electric power by single-phase group lines. The number of lamps connected to single-phase lines is regulated by normative documents. Bearing this in mind as well as the small power of LED sources single-phase group lines are usually performed with conductors of the smallest possible cross section. The limit values of the length of the calculated section that correspond to a predetermined loss of voltage in line with ambient temperature from 15 to 60 °С were determined for them. The calculations demonstrated that for group lines that feed the LEDs, the choice of conductor cross-sections in accordance with permissible voltage loss is not critical. The determinant factor for the choice of the cross-section of the conductors of group electrical networks is the calculation of acceptable heat with respect to temperature of the environment.